Report on equality between women and men, 2006 (Office for Official Publications of the European Communities, 2006)
This yearly report presents an overview of the main developments on equality between women and men in the European Union in 2005. It also outlines challenges and policy orientations for the future. The European Union reaffirmed its full commitment to gender equality in the social agenda for 2005-2010, which complements and supports the renewed Lisbon strategy for growth and jobs. Gender policies contribute to employment and growth. Three quarters of the new jobs created in the last five years in the EU have been filled by women. Still, there is a real need to step up efforts to support effective and innovative means to help men and women reconcile work and private responsibilities at all stages in their lives.